2022
DOI: 10.1080/10872981.2022.2082265
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perceptions of learning and working on the COVID-19 frontlines: ‘… a confirmation that I am in the right place professionally’

Abstract: The COVID-19 pandemic caused complex and enduring challenges for healthcare providers and medical educators. The rapid changes to the medical education landscape forced universities across the world to pause traditional medical training. In Basel, Switzerland, however, medical students had the opportunity to work on the COVID-19 frontlines. Our purpose was to understand how they perceived both learning and professional identity development in this novel context. We conducted semi-structured interviews with 21 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…As described in the introduction, resident physicians have the dual status of formal doctors and medical students, and the difficulties they face are more complex and difficult to overcome [ 21 ]. First of all, during the public health crisis, resident physicians still need to assume a lot of responsibilities in medical clinical work, which will undoubtedly increase their risk of exposure to viruses [ 22 , 53 ]. Secondly, the resident plan was severely impacted, and the planned schedule that should have taken effect was seriously affected [ 54 ]; In addition, the significant reduction in the number of patients in the inpatient service limits the education of trainees, and the disease pathological diversity exposed to trainees is significantly reduced [ 55 ]; Finally, the transformation of education mode is also a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…As described in the introduction, resident physicians have the dual status of formal doctors and medical students, and the difficulties they face are more complex and difficult to overcome [ 21 ]. First of all, during the public health crisis, resident physicians still need to assume a lot of responsibilities in medical clinical work, which will undoubtedly increase their risk of exposure to viruses [ 22 , 53 ]. Secondly, the resident plan was severely impacted, and the planned schedule that should have taken effect was seriously affected [ 54 ]; In addition, the significant reduction in the number of patients in the inpatient service limits the education of trainees, and the disease pathological diversity exposed to trainees is significantly reduced [ 55 ]; Finally, the transformation of education mode is also a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…There were other reports also showed that participants considered working on the front lines of the pandemic to be a positive learning experience, which helped improve their technical and communication skills, positively impacting their learning. 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Since a recent study by Luong et al suggested that educational adaptations and innovations implemented during the pandemic were perceived by some trainees as beneficial for fostering wellbeing (23), our purpose was to explore this finding with a unique cohort of learners. We've previously reported that medical students who volunteered at the TTC perceived the experience as meaningful in fostering their professional development and professional identity formation (16). Here, we delve into the experiences that impacted medical students' personal health and wellbeing during the pandemic.…”
Section: Introductionmentioning
confidence: 87%
“…These initiatives aimed to bolster healthcare capacities and address the surge in demands brought about by the COVID-19 pandemic (14,15). For instance, to mitigate the burden experienced by the local healthcare system, the University Hospital of Basel created an off-site Triage and Test Centre (TTC) which was located in the Preachers' Church and staffed by an interprofessional team of nurses, physicians, and military service members to screen and evaluate patients with COVID-19-like symptoms (16,17). Given their availability and eagerness to support the frontline care (18), medical students were recruited to work at the TTC voluntarily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation